DURSASANA GUGUR: SEBUAH KAJIAN RESEPTIF - Triyogo, YB. Rahno (Institut Seni Indoensia Surakarta, 2016)
The death of Dursasana in Baratayuda from time to time got a response (reception) of community supporters. Reader responses poured in various forms, such as a copy into different languages, in different forms of literature, and the performing arts. Responses occurred perhaps because literary life always offers value relefan with his time. This study is the preparation of the historical development of the story Dushasana death, either in the form of literature written and oral literature. In accordance with its objectives, this study is receptive to both approaches and methods. The final goal of this research focuses on the transformation of the death of Dursasana in the war of Baratayuda.Keywords: literature, relevant, response, various forms.